Influence of structural inversion in cooling austeunite on the character of thermal stresses in uninterruptedly cast ingot - Ju. A. Samojlovich; V. I. Tiposhpolski; G. A. Anisovich; V. A. Matochkin; I. A. Trusova (Литьë и металлургия)
On the basis of mathematical modelling of thermal and thermostressed condition of slugs during continuous casting there is studied the fact of metal embrittlement in the interval of temperatures of structure conversions. Contraction of metal and the so-called '^plasticity undershoot” is used as a criterion of steel embrittlement.